Wychowanie do życia wspólnotowego jako zadanie szkolnej lekcji religii w świetle polskich dokumentów oświatowych i katechetycznych - Kielian, Andrzej (Analecta Cracoviensia, 2013)
Upbringing is a task of both school education and catechesis. The purpose of this article is to answer the following questions: do the general aims of school education in Poland go hand in hand with the tasks of catechesis? To what extent it is possible to educate for community life (cf. GDC 86) at school religion classes in Poland? In order to find answers to these questions it is necessary to present the aims of general education in Poland according to the new core curriculum (based on the Regulation by the Minister of National Education of 23 December 2008 on Core Curricula for Pre-school and General Education in particular types of schools) along with methods for entering its records into school curricula.The general aims of upbringing, that the documents of the Church put before religious instruction at school are shown against this background, in order to find points of contact with the school curricula. The possible implementation of education for community life in the school environment is discussed on the base of the Core Curriculum for the Catechesis of the Catholic Church in Poland (approved by the Polish Bishops’ Conference in 2010).In conclusion it can be stated that the aims of both religion education at school and general education in Poland, in relation to education for community life, are similar: creation and strengthening of local communities, rooting students in natural communities, such as the family and the nation, creating a climate for dialogue between representatives of different cultures and beliefs. All these aims are focused on development of attitudes necessary for the sustainability of the community of the state. Furthermore, education for community life as the task of catechesis goes beyond the scope of school education. It calls for completion in extracurricular activities, to bring pupils to the Eucharistic community and active participation in the life and activities of the Church.